Rokok dalam Aspek Sosial-Agama Masyarakat Indonesia - Pradhana, Remo Adhy (Universitas Islam Negeri Raden Mas Said Surakarta, 2019)
Cigarette has been popular among Indonesian since 8th AD. Along with the times, people are starting to realize the dangers of smoking. Interestingly in Indonesia, one of the companies with the highest valuation on the Indonesia Stock Exchange, PT HM Sampoerna, which is a market leader in the Indonesian cigarette industry with a market share of 35%. This shows that the cigarette industry is still one of the excellent industries in Indonesia. This paper will examine how the impact of external factors represented by economic, demographic, socio-cultural, religious, and governance aspects influences the cigarette industry. This study will provide an overview of external factors that provide opportunities and threats to an industry, especially the cigarette industry. The conclusions of this study will provide a form of attitude towards the influence of external conditions for the cigarette industry so that cigarette manufacturers can formulate strategic steps to maximize the opportunities created by related external aspects.